Cardiac Resynchronization Therapy and Clinical Outcomes in Continuous Flow Left Ventricular Assist Device Recipients. Issue 12 (19th June 2018) - Gopinathannair, Rakesh; Roukoz, Henri; Bhan, Adarsh; Ravichandran, Ashwin; Ahmed, Mustafa M.; Familtsev, Dmitry; Bhat, Geetha; Cowger, Jennifer; Abdullah, Munazzah; Sandesara, Chirag; Dhawan, Rahul; Birks, Emma J.; et al.
Abstract : Background: Many patients with heart failure continue cardiac resynchronization therapy (CRT) after continuous flow left ventricular assist device (CF‐LVAD) implant. We report the first multicenter study to assess the impact of CRT on clinical outcomes in CF‐LVAD patients. Methods and Results: Analysis was performed on 488 patients (58±13 years, 81% male) with an implantable cardioverter defibrillator (ICD) (n=223) or CRT‐D (n=265) who underwent CF‐LVAD implantation at 5 centers from 2007 to 2015. Effects of CRT on mortality, hospitalizations, and ventricular arrhythmia incidence were compared against CF‐LVAD patients with an ICD alone. Baseline differences were noted between the 2 groups in age (60±12 versus 55±14, P <0.001) and QRS duration (159±29 versus 126±34, P =0.001). Median biventricular pacing in the CRT group was 96%. During a median follow‐up of 478 days, Kaplan–Meier analysis showed no difference in survival between groups (log rank P =0.28). Multivariate Cox regression demonstrated no survival benefit with type of device (ICD versus CRT‐D; P =0.16), whereas use of amiodarone was associated with increased mortality (hazard ratio 1.77, 95% confidence interval 1.1–2.8, P =0.01). No differences were noted between CRT and ICD groups in all‐cause ( P =0.06) and heart failure ( P =0.9) hospitalizations, ventricular arrhythmia incidence (43% versus 39%, P =0.3), or ICD shocks (35% versus 29%, P =0.2). During follow‐up, 69 (26%) patients underwent pulse generator replacement in the CRT‐D group compared with 36 (15.5%) in the ICD group ( P =0.003). Conclusions: In this large, multicenter CF‐LVAD cohort, continued CRT was not associated with improved survival, hospitalizations, incidence of ventricular arrhythmia and ICD therapies, and was related to a significantly higher number of pulse generator changes.